Análise do impacto de sistemas de recarga lenta de veículos elétricos em redes de distribuição secundária - Grassi, Fernando (2021)
This work presents a contextualization about electric vehicles, a technology that is gaining significant space around the world. Much because of the concern to reduce the emission of pollutants such as CO2, and in parallel with the development of sources of renewable energy generation, something that Brazil has a greater share in its electricity generation matrix. However, electric vehicles bring with them some concerns regarding the impacts they can cause to the electric grid, as it is a load that remains consuming power for several hours, and simultaneously with other vehicles. Therefore, efforts must be made so that this technology is a benefit and not an impact on an already existing system, requiring costly infrastructure adjustments to the concessionaires. Similarly, the electrical system has standards that define voltage limits that concessionaires must respect, so that energy is properly supplied to consumers. The part of the system most affected by electric vehicles is the secondary distribution, which mainly feeds residential consumers, and where most chargers are located. These chargers have their own regulations regarding various safety factors and operating voltage and current limits, however these limits are not the same as those established for the supply of voltage by utilities, which can cause electric vehicles to cause undervoltage problems. and lead to fines for the concessionaire, so it is a complex problem that needs to be better explored. This work seeks to address this problem, demonstrating how different random scenarios for the insertion of electric vehicles could cause different undervoltage problems in a real feeder. After verifying the undervoltages and respective affected buses, some charging strategies are explored, such as the gradual reduction of the recharge power, or the condition of power injection to the grid by electric vehicles, always respecting the voltage limits specified by the national standards of energy supply, both of which are satisfactory strategies to reduce or eliminate the undervoltage caused by recharging electric vehicles.